P2P Internet Financial Platform System in the Financing of Small and Medium-Sized Enterprises: A Perspective from Beijing Liwang Technology Co., Ltd. - Weili Xu (Journal of World Economy, 2025)
This paper explores the application and challenges of the P2P internet financial platform system developed by Beijing Liwang Technology Co., Ltd. in the financing of small and medium-sized enterprises (SMEs). Firstly, it introduces the basic situation, architecture, and operational mode of the P2P platform, as well as its advantages in improving financing efficiency, reducing financing costs, enhancing financing accessibility, and optimizing financing structure. Next, it analyzes the challenges faced by the platform in risk control and management, laws and regulations, market competition and sustainable development, and user trust and information security. Through case analysis, it summarizes the experiences and lessons learned from successes and failures, and proposes strategies to strengthen risk control, improve laws and regulations, enhance platform competitiveness, and strengthen user trust construction. This paper aims to provide theoretical support and practical guidance for P2P platforms to better serve the financing of SMEs.